Modeling Virtual Organization for Home Healthcare Using UML - Mahmud, Hoger (International Journal of Computer Sciences and Engineering, 2025)
Healthcare is one of the essential services required by all, technological developments in recent years have enhanced the way we receive the service. Researches show that a decentralized healthcare provision is what is required to improve quality and reduce cost. Providing healthcare at home is one way of healthcare decentralization. Home Healthcare (HHC) is gaining popularity as more and more patients prefer to receive the care in the comfort of their homes. Providing care at home requires many professionals, organizations and agencies to collaborate and work together. In this paper we apply the concept of Virtual Organization (VO) to HHC as a framework for managing the collaboration of different participants of HHC. To visualize how the VO concept may facilitate the management of possible collaboration, in this paper, we use UML use case and sequence diagram notations to model the structural and behavioral aspect VO of a HHC case study. We later evaluate the suitability of UML model in modeling VO for HHC. Our evaluation show that using the UML standard notations all aspects of HHC virtual organization cannot be modeled and therefore we suggest that UML notations require to be extend to.